Genomic and functional characterization of coleopteran insect-specific alpha-amylase inhibitor gene from amaranthus species - Bhide, Amey J.; Channale, Sonal M.; Yadav, Yashpal; Bhattacharjee, Kabita; Pawar, Pankaj K.; Maheshwari, V. L.; Gupta, Vidya S.; Ramasamy, Sureshkumar; Giri, Ashok P. (Plant Molecular Biology, 2017)
The smallest 32 amino acid alpha-amylase inhibitor from Amaranthus hypochondriacus (AAI) is reported. The complete gene of pre-protein (AhAI) encoding a 26 amino acid (aa) signal peptide followed by the 43 aa region and the previously identified 32 aa peptide was cloned successfully. Three cysteine residues and one disulfide bond conserved within known alpha-amylase inhibitors were present in AhAI. Identical genomic and open reading frame was found to be present in close relatives of A. hypochondriacus namely Amaranthus paniculatus, Achyranthes aspera and Celosia argentea. Interestingly, the 3'UTR of AhAI varied in these species. The highest expression of AhAI was observed in A. hypochondriacus inflorescence; however, it was not detected in the seed. We hypothesized that the inhibitor expressed in leaves and inflorescence might be transported to the seeds. Sub-cellular localization studies clearly indicated the involvement of AhAI signal peptide in extracellular secretion. Full length rAhAI showed differential inhibition against alpha-amylases from human, insects, fungi and bacteria. Particularly, alpha-amylases from Helicoverpa armigera (Lepidoptera) were not inhibited by AhAI while Tribolium castaneum and Callosobruchus chinensis (Coleoptera) alpha-amylases were completely inhibited. Molecular docking of AhAI revealed tighter interactions with active site residues of T. castaneum alpha-amylase compared to C. chinensis alpha-amylase, which could be the rationale behind the disparity in their IC50. Normal growth, development and adult emergence of C. chinensis were hampered after feeding on rAhAI. Altogether, the ability of AhAI to affect the growth of C. chinensis demonstrated its potential as an efficient bio-control agent, especially against stored grain pests.